The Effect of Parenting on Teenagers’ Decision to Drop out of School - Z. Deniz Aktan; Daniel Handanos (Sakarya University Journal of Education)
Previous research hasindicated the gravity of both parenting and parental bond on a child’ssuccessful upbringing. In this, four main styles of parenting have beenidentified, known as authoritarian, authoritative, permissive and neglectful. Whilerecent research addressed the role of parenting on academic success; additionalfactors include self-esteem, behavioural inhibition and behavioural activation; whereas the main types of parentalbond include affectionate constraint, affectionless control, optimal parentingand neglectful parenting. The current study takes the aforementioned researchone step further by examining if self-esteem, strength of goal orientation,parental bond and their parent’s child rearing method has an effect on ateenagers’ decision to drop out of school. Results indicated that thepermissive parenting style and affectionate constraint were the best predictorsof student’s decision to remain in education. Additionally, participants whohad decided to drop out of school displayed lower levels of self-esteem,behavioural inhibition and behavioural activation.